2017
DOI: 10.5430/jnep.v7n10p12
|View full text |Cite
|
Sign up to set email alerts
|

The influence of ethics education on awareness of nursing students with no clinical experience regarding the code of ethics: A case study

Abstract: The purpose of this study was to evaluate the influence of ethics education on Korean nursing students' awareness regarding the code of ethics. This study employed a one group pretest-posttest design. The participants were 48 sophomore nursing students with no clinical experience from a city in Korea. In this study, ethics education involved lectures related to "nursing ethics and professionalism". Data were collected in September and December 2016. The collected data were analyzed using means, standard deviat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…In agreement with our findings, the Ertuğ et al (26) study in Turkey also showed that the moral sensitivity of nurses is influenced by education and level education. The results of the Kang study (27) in Korea also indicated that ethics education is necessary to create a desirable moral value system among nursing students.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with our findings, the Ertuğ et al (26) study in Turkey also showed that the moral sensitivity of nurses is influenced by education and level education. The results of the Kang study (27) in Korea also indicated that ethics education is necessary to create a desirable moral value system among nursing students.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies showed that participate in workshops and congresses related to medical ethics can affect knowledge and awareness of medical sciences students in this regard. [ 16 17 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies reviewed in nursing found that ethics courses and content, whether a formal course or continuing education experience, related to increased moral awareness 49 and to moral sensitivity and ethical reasoning ability. 5 One explanation for our finding might be that courses in ethics taken by the respondents pre-dated students’ junior and senior years.…”
Section: Discussionmentioning
confidence: 99%